Upadacitinib Reduces Crohn's Disease Symptoms Within the First Week of Induction Therapy - Colombel, Jean Frédéric; Hisamatsu, Tadakazu; Atreya, Raja; Bresso, Francesca; Thin, Lena; Panaccione, Remo; Parra, Rogério Serafim; Ford, Sharanya; Remple, Valencia P.; Lacerda, Ana Paula; Anyanwu, Samuel I.; Mallick, Madhuja; et al. (Clinical Gastroenterology and Hepatology, 2024)
Background & Aims: Upadacitinib (UPA), an oral Janus kinase inhibitor, is approved to treat moderately to severely active Crohn's disease (CD). Because symptomatic response is an important initial treatment goal for patients, we evaluated the rapidity of symptomatic improvement in patients with CD receiving UPA 45 mg once daily (UPA45) induction therapy. Methods: This post hoc analysis included pooled data from 2 phase 3, multicenter, double-blind, 12-week induction trials (U-EXCEL and U-EXCEED) and 1 maintenance trial (U-ENDURE). Daily diary data for the first 15 days of UPA45 or placebo (PBO) treatment were used to analyze improvement in very soft/liquid stool frequency (SF) and abdominal pain score (APS). Clinical outcomes were evaluated at every study visit. Results: Overall, 1021 patients (n = 674 UPA45; n = 347 PBO) were analyzed. UPA45 demonstrated greater efficacy vs PBO for SF <3 and APS ≤1, providing rapid relief by day 5 or 6, regardless of prior biologic exposure. Mean changes in SF and APS were greater with UPA45 beginning at week 2 (−2.0 and −0.5, respectively; P < .001) and were maintained through week 12 (−3.0 and −1.0, respectively; P < .001) vs PBO. The first achievement of daily SF/APS clinical remission occurred earlier with UPA45 (median, 13 d) vs PBO (median, 32 d), and patients treated with UPA45 showed improved rates of SF/APS clinical remission (21.1% UPA45 vs 8.9% PBO) and clinical response (58.8% UPA45 vs 37.9% PBO) starting at week 2 (both P ≤ .01). Conclusions: UPA45 provided rapid relief of clinical symptoms within the first week of treatment in patients with CD. ClinicalTrials.gov numbers: NCT03345849, NCT03345836, and NCT03345823.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Crohn's Disease; Rapid Symptom Relief; Upadacitinib